The Relationship of Early Mobilization and Wound Healing of Inflammation Phase among Post Cesarean Section Women at PMI Hospital Bogor West Java - Tommy J Wowor; Larasati Dwi; Naziyah Taufik djafar (Nursing and Health Sciences Journal (NHSJ), 2022)
Early mobilization is one of postpartum maternal care mobilization which is important to accelerate recovery, the lack of mobilization will make the women condition worsen. Based on interviews conducted with 5 respondents of post cesarean section patients in Gardenia Room of PMI Bogor Hospital, out of 5 respondents 3 of them said they did not practice early mobilization because they felt anxious in the area of post cesarean section injury.This study aims to determine the relationship between early mobilization and the process of wound healing of inflammation phase among post caesarean section women in Gardernia Room of PMI Bogor West Java. The researcher used descriptive correlational with cross sectional approach. The sample used in this study is total sampling. The instruments used in this study consisted of demographic quetionnaires, respondent characteristics, early mobilization, early mobilization observation sheets anda BWAT questionnaires. Data are annalyzed using Chi-Square test to find out whether there is an effect of mobilization on the post casarean section wound healing process.The results showed that there is an effect of early mobilization on wound healing process of inflammation phase among post caesarean section women with a p value of 0,000. Early Mobilization is very important to reduce the risks of prolonged bed rest and is done to help heal post operative caesarean sores and also could improve the Nursing planning program for wound healing process for women post SC specific by phase of inflammation.